A Modelling Language for Discourse Analysis in Humanities: Definition, Design, Validation and First Experiences - Martin Rodilla, Patricia; González-Pérez, César (Revista de Humanidades Digitales, 2017)
Due to humanities generally produce knowledge in textual formats (e.g. narrative conclusions or reports), a properly management of the humanities corpus needs methods for conceptualizing and extracting information from textual sources. Discourse analysis techniques allow extracting information in terms of the connection between discourse structure and elements of the reality referred in the text, as well as the inferential dimension. This semantic information is not available following other extraction methods from texts. In order to formalize the discourse analysis application for textual sources in humanities, a modelling language has been defined and initially validated with humanities specialists, showing the discourse structure and the semantic and inferential aspects extracted.